Epigenetic modifications of gene promoter DNA in the liver of adult female mice masculinized by testosterone. Issue 145 (January 2015) - Dkhil, Mohamed A.; Al-Quraishy, Saleh; Abdel-Baki, Abdel-Azeem; Ghanjati, Foued; Arauzo-Bravo, Marcos J.; Delic, Denis; Wunderlich, Frank
Highlights: Epigenetic reprogramming by testosterone (T) of promoter gene DNA in the liver of female mice. T induces long-lasting hyper- and hypo-methylations of DNA of 47 and 35 gene promoters. T does not modify promoter DNA of T-responsive male- and female-predominant genes. Abstract: Testosterone (T) is known to masculinize the female phenotype of the liver, evidenced as up- and down-regulated expressions of male- and female-predominant genes, respectively, involved in hepatic metabolism. This study is aimed at identifying epigenetic modifications of promoters of these differently expressed genes in the liver after masculinization by T of adult female C57BL/6 mice using methylated DNA immunoprecipitation and NimbleGen microarrays. Among the 17, 354 promoters examined, 82 promoters in the liver have been identified to be significantly changed by T ( p < 0.05), with 47 and 35 promoters exhibiting increased and decreased DNA methylation, respectively. Most of these promoters display the changes of DNA methylation in their Ups-regions, which are between +500 and +2000 bp upstream from the transcription start site (TSS) of the genes. Less T-induced modifications have been detected in the Cor-regions of the promoters, i.e., +500 to −500 bp around the TSS. Only 13 and 7 Cor-promoters are hyper- and hypo-methylated, respectively, among which are 10 hyper- and 5 hypo-methylated promoters of genes with annotated functions. Surprisingly, the promoters are largely unmethylated in those genes whose expression has been previously found to be permanently deregulated by T in the liver, as e.g. the T-upregulated male-predominant genes Cyp7b1, Cyp2d9, Cyp4a10, Ugt2b1, Ugt2b38, Hsd3b5, Slco1a1 as well as the T-downregulated female-predominant genes Cyp2b9, Cyp2b13, Cyp3a41, Cyp3a44, Fmo3, Sult2a2, respectively. Though methylatable, the promoter DNA of Ar, Esr1, and Esr2 remained unaffected by T . However, T decreases DNA-methylation of the Cor-promoter region of Ddc encoding the AR-coactivator dopa decarboxylase. Among the identified 15 Cor-promoters of genes with annotated functions are also those of Defb43, Cst11, and Sele involved in innate immunity. Our data support the view that T may exert long-lasting epigenetic effects on functions of the liver-inherent immune system.